Pengembangan Virtual Reality untuk Simulasi Tindakan Asuhan Persalinan Normal: (Studi Kasus Fakultas Kedokteran Universitas Pendidikan Ganesha) - I Ketut Bayu Dilananda Septiawan; I Gede Partha Sindu; I Gede Bendesa Subawa (Universitas Pendidikan Ganesha, 2025)
Normal childbirth is crucial for hands-on practice, and numerous simulations are conducted by midwifery students. In this case study, midwifery students at Undiksha face challenges such as work-from-home conditions and pathological risks which hinder their ability to engage in direct practice. The lack of immersive learning media is another issue, as the media typically used for practice is limited to videos, which do not provide an immersive experience. To address this, this research developed a Virtual Reality (VR) application using the MDLC (Multimedia Development Life Cycle) model for normal childbirth simulation. The application was created using Unity Engine, Blender, and the Oculus Integration package, aiming to enhance the understanding and practical skills of midwifery students at Universitas Pendidikan Ganesha (Undiksha). The development stages included conceptualization, design, material collection, creation, testing, and distribution. Testing results showed that the application is valid and suitable for use as a learning tool. Tests with OVR, media experts, and content experts yielded excellent results, while field testing using the UEQ instrument resulted in an overall rating of